Temporal expression of mitochondrial life cycle markers during acute and chronic overload of rat plantaris muscles - Hyatt, Jon-Philippe K.; Lu, Emilie J.; McCall, Gary E. (Frontiers in Physiology, 2024)
Skeletal muscle hypertrophy is generally associated with a fast-to-slow phenotypic adaptation in both human and rodent models. Paradoxically, this phenotypic shift is not paralleled by a concomitant increase in mitochondrial content and aerobic markers that would be expected to accompany a slow muscle phenotype. To understand the temporal response of the mitochondrial life cycle (i.e., biogenesis, oxidative phosphorylation, fission/fusion, and mitophagy/autophagy) to hypertrophic stimuli, in this study, we used the functional overload (FO) model in adult female rats and examined the plantaris muscle responses at 1 and 10 weeks. As expected, the absolute plantaris muscle mass increased by ∼12 and 26% at 1 and 10 weeks following the FO procedure, respectively. Myosin heavy-chain isoform types I and IIa significantly increased by 116% and 17%, respectively, in 10-week FO plantaris muscles. Although there was a general increase in protein markers associated with mitochondrial biogenesis in acute FO muscles, this response was unexpectedly sustained under 10-week FO conditions after muscle hypertrophy begins to plateau. Furthermore, the early increase in mito/autophagy markers observed under acute FO conditions was normalized by 10 weeks, suggesting a cellular environment favoring mitochondrial biogenesis to accommodate the aerobic demands of the plantaris muscle. We also observed a significant increase in the expression of mitochondrial-, but not nuclear-, encoded oxidative phosphorylation (OXPHOS) proteins and peptides (i.e., humanin and MOTS-c) under chronic, but not acute, FO conditions. Taken together, the temporal response of markers related to the mitochondrial life cycle indicates a pattern of promoting biogenesis and mitochondrial protein expression to support the energy demands and/or enhanced neural recruitment of chronically overloaded skeletal muscle.